Commissioning of a hybrid readout TPC test set-up and gas gain simulations. Issue 1 (1st November 2022) - Deisting, A.
Abstract : A hybrid readout Time Projection Chamber (TPC) has a simultaneous optical- and charge readout. The optical readout provides 2D images of particle tracks in the active volume, whilst the charge readout provides additional information on the particle position perpendicular to the image plane. A hybrid readout TPC working at high pressure is an attractive device for physics cases where an excellent space point resolution and a high target density is required as e.g. measuring a neutrino beam at the source of a long baseline neutrino oscillation experiment. In this paper we present two different lines of work towards the goal of developing hybrid TPC technology: a) Commissioning of a set-up with gas electron multipliers employing optical and charge readout. b) An analytical parametrisation of the gas gain for a multi wire proportional chamber based on GARFIELD++ simulations, which – when validated with measurements – allows to skip these simulations in the future altogether.